Correlation between lattice deformations and optical properties of Ni doped ZnO at dilute concentration. (2020) - Kaur, Puneet; Rahul,; Kaur, Simranpreet; Kriti,; Arora, Deepawali; Asokan, Kandasami; Paul Singh, Davinder
Abstract: The present studies concentrates on the structural and optical properties of Ni doped ZnO nanoparticles at dilute concentration. These compounds were synthesized via organic co-precipitation route. The resultant nanoparticles were characterized using X-ray diffraction (XRD), UV–Vis spectroscopy, Photoluminescence (PL) spectroscopy. The XRD spectra confirm the hexagonal wurtzite structure with space group P63mc with polycrystalline nature of Ni-ZnO and pristine sample. The results of Williamson Hall analysis shows a similar trend to that obtained by Scherrer's equation. The similarity in the values of average particle size (D) for each sample calculated via uniform deformation model (UDM), uniform stress deformation model (USDM), uniform deformation energy density model (UDEDM) clearly indicates the presence of the micro strain. High value of estimated lattice strain confirms about the polycrystalline behavior as indicated from the XRD diffraction pattern. PL studies confirm the enhancement in the defect structure and oxygen vacancies in the host system with the incorporation of dopant ions leading to strain which is in agreement with the peak shift in the XRD. These defects are responsible for the small red shift in the band gap, as indicated from UV–Vis measurements. The spectral chromaticity coordinates obtained from PL indicates that the light emission under UV excitation changes from bluish green to blue region with the addition of Ni making them promising candidates for the use as cost effective phosphors in UV-green blue region and in down conversion based luminescent devices.